Isolation and enzymatic studies of dye-degrading white-rot fungus - Abdul Aziz, Ahmad Afif (2013)
Dye is present continuously in the environment. They are designed to be permanent and resistant to degradation by their physical and chemical properties. Therefore, increasing discharge and improper management of solid and liquid industrial dye wastes have generated a great concern among industrialists and the scientific community due to their negative effects. To date, effective method to treat recalcitrant dye is still lacking, to ensure safe disposal of dye effluents. In this regards, this study had been designated to isolate and screen dye degrading white rot fungi from local environments in Peninsular Malaysia; to identify the selected white rot fungus that showed the best degrading ability; to evaluate the degradation of azo dye by the selected white-rot fungus and determine its optimum conditions; and to partially purify and partially characterize the ligninolytic enzyme. Thirty nine white rot fungi (WRF) from soil and wood samples were isolated in Selangor, Kelantan,Pahang and Terengganu and tested for their capability to degrade textile azo dyes (Orange G (C.I. 16230), Ponceau 2R (C.I. 16450), Amaranth (C.I. 16185), Trypan Blue (C.I. 23850) dan Direct Blue 71 (C.I. 34140). Thirty-three isolates showed positive results with varying degrees of dye degradation. Two isolates (Isolate 4-UPM and Isolate 17-UPM) from Universiti Putra Malaysia (UPM) campus in Selangor were selected for further studies owing to their ability to completely decolourize all the azo dyes within the shortest time. Qualitative study on defined solid media showed Isolate 17-UPM and Isolate 4-UPM were capable of degrading all five dyes under nitrogen-limiting conditions, with glucose as the source of energy. When cultured in two-stage liquid medium for quantitative screening, Isolate 17-UPM degradation rate was in the range of 96 to 99% of 0.2 g/L while Isolate 4-UPM showed a range of 38 to 96 % of all the tested azo dyes. Both isolates degraded the dyes within one to ten days at different rates. Isolate 17-UPM and Ponceau 2R were used for further studies. Overall, the degradation rates of Isolate 17-UPM in agitated cultures were higher by nearly ten times compared to static cultures. Ponceau 2R was degraded optimally when incubated between 35 to 40°C in agitated cultures at the initial pH of 6. The assays for lignin modifying enzymes involved in the azo dye degradation showed the presence of laccase only, while lignin peroxidase and manganese peroxidases were absent. There was a significant correlation between the laccase activity profile in agitated liquid cultures and the azo dye degradation profile where both optimum temperature and initial pH were 40°C and pH 6, respectively. The laccase produced by Isolate 17-UPM during azo dye degradation was partially purified using DEAE Cellulose anion exchanger and ZorbaxR GF-250 gel filtration column. The partial purified enzyme showed a Km (app) value of 0.28 mM, Vmax (app) value of 100 μmol/min.ml, optimum temperature activity at 40 to 50°C and pH 3.0 to 5.0 when 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonate) (ABTS) was used as the substrate. It was also shown to be most stable at room temperature and pH 6.0 to 7.0.The Isolate 17-UPM was further characterized at molecular level through ITS region gene sequencing. The internal transcribe spacer region of the isolated DNA was amplified by PCR using the primers recognized as, primer ITS 1F and ITS 4. Isolate 17-UPM was identified as Coriolopsis sp. strain aff17. In this study, a whiterot fungus capable of degrading azo dyes was isolated, identified and optimized for dye degradation, and the enzyme involved was partially purified and characterized.